Titanium bipolar plate conductive corrosion-resistant coating and preparation method thereof
By forming the In/Sn-TiOx conductive layer and the TiO2 oxide layer on the titanium bipolar plate, the corrosion problem of the titanium plate in the proton exchange membrane electrolytic cell anode environment is solved, and a coating with high conductivity and corrosion resistance is achieved. Reduces cost and complexity and significantly improves the performance of the electrolytic cell.
Patent Information
- Application Number
- CN202411634975.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-01-07
AI Technical Summary
Titanium bipolar plates are prone to corrosion in the anode environment of proton exchange membrane electrolytic cells, resulting in reduced conductivity and increased ohmic overpotentials. The existing precious metal coatings are costly and the preparation process is complex, and the existing metal nitride coatings are strong. It is easy to form a passivation film in an oxidizing environment, which is difficult to meet the dual requirements of corrosion resistance and electrical conductivity.
In/Sn-TiOx is used as the conductive layer material, covering the TiO2 oxide layer, and the composite coating is formed by electrophoretic deposition and high-temperature heat treatment, which improves the conductivity and corrosion resistance of the titanium plate, reduces the interface contact resistance, and is simple and economical. The preparation process is realized.
It significantly reduces the corrosion current density of the titanium plate, improves conductivity, reduces the interface contact resistance by half, and the coating exhibits excellent adhesion and corrosion resistance in harsh environments, reducing the risk of physical damage during the use of the electrolytic cell .
Smart Images

Figure CN119265583A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating materials, and in particular to a conductive and corrosion-resistant coating for a titanium bipolar plate. Background Art
[0002] In the operation of proton exchange membrane electrolyzer (PEMWE), the anode works in a harsh environment of high potential and strong oxidation, which places extremely high demands on the corrosion resistance of electrolyzer materials. Titanium is usually selected as the material for electrolyzer bipolar plates and anode porous transport layers due to its low density, high strength, excellent chemical stability and corrosion resistance.
[0003] However, a stable natural oxide film is easily formed on the surface of titanium. Although this film can prevent further oxidation or corrosion of titanium, it also has an adverse effect on its electrical conductivity and thermal conductivity, increasing the interface contact resistance between the porous transport layer and the catalyst layer, and between the bipolar plate and the porous transport layer, resulting in an increase in the ohmic overpotential during the operation of the electrolyzer.
[0004] Moreover, the commonly used proton exchange membrane is a fluorine-containing perfluorosulfonic acid (PFSA) membrane, in which the fluoride ions (F-) will attack the oxide film on the titanium surface, causing damage to the protective layer on the titanium surface, thereby shortening the service life of the electrolytic cell.
[0005] To address this situation, researchers have tried to use precious metals such as platinum (Pt) and gold (Au) as coatings to improve the corrosion resistance and conductivity of titanium, but this significantly increases the cost of electrolyzers and green hydrogen production. Therefore, researchers have conducted a lot of research work to reduce the use of precious metals. Current research focuses on the application of coatings of metals such as titanium, tantalum, niobium and their nitrides. However, these metals are prone to form passivation films that deteriorate conductivity in a strong oxidizing environment, and metal nitrides often passivate and corrode in practical applications. In addition, most of the existing preparation methods rely on complex and costly technologies such as magnetron sputtering (MS) and vacuum plasma spraying (VPS), which often have problems such as low target utilization and excessive energy consumption. Therefore, it is of great practical significance and urgent need to develop a non-precious metal coating with high conductivity and strong corrosion resistance suitable for bipolar plates of proton exchange membrane electrolyzers through economical and efficient preparation methods. Summary of the invention
[0006] The embodiment of the present application provides a conductive corrosion-resistant coating for a titanium bipolar plate, which aims to solve the corrosion problem faced by the anode side of a proton exchange membrane electrolyzer in a harsh working environment, and provides a coating with a simple preparation process, low cost and high corrosion resistance.
[0007] In order to solve the above technical problems, the technical solution proposed in this application is:
[0008] A conductive corrosion-resistant coating for a titanium bipolar plate, comprising: a conductive layer and an oxide layer;
[0009] The oxide layer covers the titanium base layer, and the conductive layer covers the oxide layer; wherein,
[0010] The conductive layer material is In / Sn-TiO x , where x ranges from 1.3 to 2.2;
[0011] The oxide layer material is TiO2.
[0012] The present application also claims a method for preparing the conductive corrosion-resistant coating of the titanium bipolar plate as described above, comprising the following steps:
[0013] S1: providing a uniformly mixed powder of In2O3 and SnO2;
[0014] S2: using one or more of ethanol, methanol, n-propanol, isopropanol, n-butanol, ethylene glycol, acetone, acetylacetone and water as solvents, preparing a 5-15 g / L colloidal solution;
[0015] S3: adding a cationic polymer to the colloidal solution, wherein the mass ratio of the mixed powder to the cationic polymer is in the range of 0.1-0.4, and the cationic polymer is polyethyleneimine (PEI), polyacrylamine (PAM) or polypyrrole (PPy) containing a cationic group;
[0016] S4: providing a titanium plate as a substrate;
[0017] S5: Use a graphite plate as an anode and a titanium plate as a cathode, place them in the colloidal solution prepared above, apply a voltage of 2-30V, and deposit for 60-600s;
[0018] S6: The deposited coating is treated under high-temperature inert gas protection at a temperature of 950°C-1250°C and a heat preservation time of 60min-180min.
[0019] Furthermore, before S1, it also includes:
[0020] S0: Titanium plate pretreatment
[0021] First, the titanium plate is ground and polished, and then the titanium plate is ultrasonically cleaned;
[0022] Then, the titanium plate is etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate;
[0023] Furthermore, after S5, it also includes:
[0024] S51: After the electrophoretic deposition process is completed, the sample is placed in a vacuum drying oven at 60° C. for vacuum drying for 12 h, and then vacuum dried at 100° C. for 1 h.
[0025] Furthermore, the S6 specifically includes:
[0026] The dried sample is placed in an alumina crucible, put into a tubular furnace, and heated to 950-1250°C at a heating rate of 5°C / min under the protection of high-purity argon for heat treatment, and kept at this temperature for 60-180 minutes. After cooling in the furnace, a conductive and corrosion-resistant composite coating is obtained.
[0027] Further, in S1, the provided mixed powder of In2O3 and SnO2, wherein the molar amount of Sn element in the mixed powder accounts for 0-100% of the total molar amount of In and Sn;
[0028] Furthermore, the material of the titanium plate is a titanium plate with a Ti content greater than 80 wt.%.
[0029] Furthermore, the colloidal solution in step S2 is a 12 g / L colloidal solution prepared with anhydrous ethanol as solvent, which contains 1.56 g of mixed powder of In2O3 and SnO2 and 130 ml of anhydrous ethanol, and the molar amount of Sn element in the mixed powder accounts for 4.6% of the total molar amount of In and Sn.
[0030] Furthermore, the electrochemical parameters of the coating are:
[0031] At 70℃, 0.5mM H2SO4+5ppm F - The corrosion potential E of the coating compared to the silver-silver chloride electrode in the electrolytic cell anode working solution environment corr is -95.9mV, the corrosion current density I corr 0.258μA / cm 2 , the interface contact resistance ICR is 15.94mΩ·cm 2 .
[0032] The present application also claims protection for an anode titanium plate for a proton exchange membrane electrolyzer, comprising a titanium base layer and a coating as described above covering the titanium base layer.
[0033] Compared with the prior art, the conductive and corrosion-resistant coating for titanium bipolar plates of the present invention has achieved the following beneficial technical effects:
[0034] 1. The present invention first forms a titanium oxide layer by artificial induction, and then dopes In and Sn elements into the oxide layer to form a solid solution In / Sn-TiO xThe conductive layer can enhance the conductivity of the oxide layer and the interface contact resistance (15.94mΩ·cm 2 ) is a titanium plate without composite coating (66.94mΩ·cm 2 ) and has good electrical conductivity.
[0035] 2. The main component of the present invention is an artificially passivated oxide layer, which has stable performance in a strong oxidizing environment and can protect the titanium plate from corrosion in a harsh environment. - ), corrosion current density (0.258μA / cm 2 ) is lower than that of titanium plate without composite coating (2.14μA / cm 2 ) was reduced by one order of magnitude and showed a lower current density (3.27 μA / cm 2 ), has good corrosion resistance.
[0036] 3. The present invention prepares the composite coating by a two-step method of electrophoretic deposition and high-temperature heat treatment. In this process, no chemical reaction occurs during the electrophoretic deposition process. The colloidal solution used can be recovered and reused after high-speed centrifugal separation. At the same time, the equipment requirements are low, the operation process is simple, it has good economy, and it is easy to promote.
[0037] 4. After the metal oxide is deposited by electrophoresis, the present invention causes a chemical reaction between the metal oxide and the titanium plate during a high-temperature heat treatment process to form a composite coating with a strong chemical adhesion effect, and an artificially induced oxide layer and a conductive layer, which have excellent adhesion and can resist physical damage during the use of the electrolytic cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0039] Figure 1 Schematic diagram of the layers in the cross section of the composite coating
[0040] Figure 2 The composite coating provided in Example 1 was in 0.5 mM H2SO4 + 5 ppm F - Potentiodynamic polarization curves in solution
[0041] Figure 3The composite coating provided in Example 1 was in 0.5 mM H2SO4 + 5 ppm F - 2V constant potential polarization curve in solution
[0042] Figure 4 The graph of the interface contact resistance of the conductive corrosion-resistant composite coating on the surface of a titanium plate provided in Example 1 as a function of pressure DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] like Figure 1-4 As shown, a conductive corrosion-resistant coating for a titanium bipolar plate according to an embodiment of the present application comprises: a conductive layer 1 and an oxide layer 2;
[0045] The oxide layer covers the titanium base layer 3, and the conductive layer 1 covers the oxide layer 2; wherein,
[0046] The conductive layer material 1 is made of In / Sn-TiO x , where x ranges from 1.3 to 2.2;
[0047] The material of the oxide layer 2 is TiO2.
[0048] Furthermore, the method for preparing the conductive corrosion-resistant coating of the titanium bipolar plate comprises the following steps:
[0049] S1: providing a uniformly mixed powder of In2O3 and SnO2;
[0050] S2: using one or more of ethanol, methanol, n-propanol, isopropanol, n-butanol, ethylene glycol, acetone, acetylacetone, and water as solvents to prepare a 5-15 g / L colloidal solution;
[0051] S3: adding a cationic polymer to the colloidal solution, wherein the mass ratio of the mixed powder to the cationic polymer is in the range of 0.1-0.4, and the cationic polymer is polyethyleneimine (PEI), polyacrylamine (PAM) or polypyrrole (PPy) containing a cationic group;
[0052] S4: providing a titanium plate as a substrate;
[0053] S5: Use a graphite plate as an anode and a titanium plate as a cathode, place them in the colloidal solution prepared above, apply a voltage of 2-30V, and deposit for 60-600s;
[0054] S6: The deposited coating is treated under high-temperature inert gas protection at a temperature of 950°C-1250°C and a heat preservation time of 60min-180min.
[0055] Preferably, before S1, the method further includes:
[0056] S0: Titanium plate pretreatment
[0057] First, the titanium plate is ground and polished, and then the titanium plate is ultrasonically cleaned;
[0058] Then, the titanium plate is etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate;
[0059] Preferably, after S5, the method further includes:
[0060] S51: After the electrophoretic deposition process is completed, the sample is placed in a vacuum drying oven at 60° C. for vacuum drying for 12 h, and then vacuum dried at 100° C. for 1 h.
[0061] Preferably, the S6 specifically includes:
[0062] The dried sample is placed in an alumina crucible, put into a tubular furnace, and heated to 950-1250°C at a heating rate of 5°C / min under the protection of high-purity argon for heat treatment, and kept at this temperature for 60-180 minutes. After cooling in the furnace, a conductive and corrosion-resistant composite coating is obtained.
[0063] Preferably, the cationic group comprises an amino group or an amine group.
[0064] The present application is further described below in conjunction with embodiments:
[0065] Example 1
[0066] First, the titanium plate was polished with a diamond grinding disc, an MD Largo grinding disc and a polishing cloth, and then ultrasonically cleaned with acetone, ethanol and deionized water. Subsequently, the titanium plate was etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate sample. 130 ml of anhydrous ethanol and 1.56 g of a mixed powder of In2O3 and SnO2 (the molar amount of Sn element accounts for 4.6% of the total molar amount of In and Sn) were prepared into a 12 g / L colloidal solution, and then 0.39 g of cationic polymer polyethyleneimine (the mass ratio of mixed powder: cationic polymer is 0.25) was added, and ultrasonic dispersion was first performed for 10 to 30 minutes, followed by 12 hours of magnetic stirring, and then ultrasonic dispersion was performed for another 30 minutes to break up the agglomerates. A graphite plate was used as the anode and a pretreated titanium plate was used as the cathode. The anode and the cathode were placed in the colloidal solution prepared above, with a distance of about 15 mm. A constant voltage of 8 V was applied and the deposition lasted for 180 seconds. After the electrophoretic deposition process was completed, the sample was placed in a vacuum drying oven at 60°C for vacuum drying for 12 hours, and then vacuum dried at 100°C for 1 hour to remove a small amount of moisture in the coating. The dried sample was placed in an alumina crucible and placed in a tubular furnace under the protection of high-purity argon gas at a heating rate of 5°C / min to 1000°C for heat treatment, and maintained at this temperature for 2 hours. After cooling in the furnace, a conductive and corrosion-resistant composite coating was obtained.
[0067] Example 2
[0068] First, the titanium plate was polished with a diamond grinding disc, an MD Largo grinding disc and a polishing cloth, and then ultrasonically cleaned with acetone, ethanol and deionized water. Subsequently, the titanium plate was etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate sample. 130 ml of anhydrous ethanol and 1.56 g of a mixed powder of In2O3 and SnO2 (the molar amount of Sn element accounts for 4.6% of the total molar amount of In and Sn) were prepared into a 12 g / L colloidal solution, and then 0.39 g of cationic polymer polyethyleneimine (mixed powder: cationic polymer mass ratio 0.25) was added, first ultrasonically dispersed for 10 to 30 minutes, then magnetically stirred for 12 hours, and then ultrasonically dispersed for another 30 minutes to break up the agglomerates. A graphite plate was used as the anode and a pretreated titanium plate was used as the cathode. The anode and the cathode were placed in the colloidal solution prepared above, with a distance of about 15 mm. A constant voltage of 10 V was applied and the deposition lasted for 180 seconds. After the EPD process was completed, the sample was placed in a vacuum drying oven at 60°C for vacuum drying for 12 hours, and then vacuum dried at 100°C for 1 hour to remove a small amount of moisture in the coating. The dried sample was placed in an alumina crucible and placed in a tubular furnace under the protection of high-purity argon at a heating rate of 5°C / min to 1100°C for heat treatment, and maintained at this temperature for 2 hours. After cooling in the furnace, a conductive and corrosion-resistant composite coating was obtained.
[0069] Example 3
[0070] First, the titanium plate was polished with a diamond grinding disc, an MD Largo grinding disc and a polishing cloth in sequence, and the titanium plate was ultrasonically cleaned with acetone, ethanol and deionized water. Subsequently, the titanium plate was acid-etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate sample. 130 ml of anhydrous ethanol and 1.56 g of a mixed powder of In2O3 and SnO2 (the molar amount of the Sn element accounts for 0% of the total molar amount of In and Sn) were prepared into a 12 g / L colloidal solution, and then 0.468 g of cationic polymer polyethyleneimine (mixed powder: cationic polymer mass ratio 0.25) was added, first ultrasonically dispersed for 10 to 30 minutes, then magnetically stirred for 12 hours, and then ultrasonically dispersed for another 30 minutes to break the agglomerates. A graphite plate was used as an anode and a pretreated titanium plate was used as a cathode, and placed in the colloidal solution prepared above, where the distance between the anode and the cathode was about 15 mm, a constant voltage of 10 V was applied, and the deposition was 180 seconds. After the EPD process is completed, the sample is placed in a vacuum drying oven at 60°C for 12 hours, and then vacuum dried at 100°C for 1 hour to remove a small amount of moisture in the coating. The dried sample is placed in an alumina crucible and placed in a tubular furnace for heat treatment at a heating rate of 5°C / min to 1250°C under the protection of high-purity argon gas, and maintained at this temperature for 2 hours. After cooling in the furnace, a conductive and corrosion-resistant composite coating is obtained.
[0071] Example 4
[0072] First, the titanium plate was ground and polished in sequence using a diamond grinding disc, an MD Largo grinding disc and a polishing cloth, and the titanium plate was ultrasonically cleaned with acetone, ethanol and deionized water. Subsequently, the titanium plate was acid-etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate sample. 130 ml of anhydrous ethanol and 1.56 g of a mixed powder of In2O3 and SnO2 (the molar amount of the Sn element accounts for 50% of the total molar amount of In and Sn) were prepared into a 12 g / L colloidal solution, and then 0.468 g of cationic polymer polyethyleneimine (mixed powder: cationic polymer mass ratio 0.3) was added, first ultrasonically dispersed for 10 to 30 minutes, then magnetically stirred for 12 hours, and then ultrasonically dispersed for another 30 minutes to break the agglomerates. A graphite plate was used as an anode and a pretreated titanium plate as a cathode, and placed in the colloidal solution prepared above, where the distance between the anode and the cathode was about 15 mm, a constant voltage of 8 V was applied, and the deposition was 180 seconds. After the EPD process is completed, the sample is placed in a vacuum drying oven at 60°C for 12 hours, and then vacuum dried at 100°C for 1 hour to remove a small amount of moisture in the coating. The dried sample is placed in an alumina crucible, placed in a tubular furnace, and heat treated at a heating rate of 5°C / min to 1000°C under the protection of high-purity argon gas, and maintained at this temperature for 2 hours. After cooling in the furnace, a conductive and corrosion-resistant composite coating is obtained.
[0073] Example 5
[0074] First, the titanium plate was ground and polished in sequence using a diamond grinding disc, an MD Largo grinding disc and a polishing cloth, and the titanium plate was ultrasonically cleaned with acetone, ethanol and deionized water. Subsequently, the titanium plate was acid-etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate sample. 130 ml of anhydrous ethanol and 1.56 g of a mixed powder of In2O3 and SnO2 (the molar amount of the Sn element accounts for 100% of the total molar amount of In and Sn) were prepared into a 12 g / L colloidal solution, and then 0.312 g of cationic polymer polyethyleneimine (mixed powder: cationic polymer mass ratio 0.2) was added, first ultrasonically dispersed for 10 to 30 minutes, then magnetically stirred for 12 hours, and then ultrasonically dispersed for another 30 minutes to break the agglomerates. A graphite plate was used as an anode and a pretreated titanium plate as a cathode, and placed in the colloidal solution prepared above, where the distance between the anode and the cathode was about 15 mm, a constant voltage of 6 V was applied, and the deposition was 180 seconds. After the EPD process is completed, the sample is placed in a vacuum drying oven at 60°C for 12 hours, and then vacuum dried at 100°C for 1 hour to remove a small amount of moisture in the coating. The dried sample is placed in an alumina crucible and placed in a tubular furnace for heat treatment at a heating rate of 5°C / min to 950°C under the protection of high-purity argon gas, and maintained at this temperature for 2 hours. After cooling in the furnace, a conductive and corrosion-resistant composite coating is obtained.
[0075] After the above examples were implemented, the titanium plate with the composite coating was placed in a three-electrode test device and tested under the simulated working conditions of the anode side of the PEM electrolyzer (70°C, 0.5 mM H2SO4 + 5 ppm F - The results are shown in Figure 2-3 At the same time, the conductivity was evaluated using the ICR-SI interface contact resistance meter from Zhejiang Xinpu Interface Equipment Technology Co., Ltd. The results are shown in Figure 4 .
[0076] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A conductive and corrosion-resistant coating for a titanium bipolar plate, characterized in that: include: Conductive layer and oxide layer; The oxide layer covers the titanium base layer, and the conductive layer covers the oxide layer; wherein, The conductive layer material is In / Sn-TiO x , where x ranges from 1.3 to 2.2; The oxide layer material is TiO2.
2. A method for preparing a conductive corrosion-resistant coating for a titanium bipolar plate as claimed in claim 1, characterized in that: The following steps are involved: S1: providing a uniformly mixed powder of In2O3 and SnO2; S2: using one or more of ethanol, methanol, n-propanol, isopropanol, n-butanol, ethylene glycol, acetone, acetylacetone and water as solvents, preparing a 5-15 g / L colloidal solution; S3: adding a cationic polymer to the colloidal solution, wherein the mass ratio of the mixed powder to the cationic polymer is in the range of 0.1-0.4, and the cationic polymer is polyethyleneimine (PEI), polyacrylamine (PAM) or polypyrrole (PPy) containing a cationic group; S4: providing a titanium plate as a substrate; S5: Use a graphite plate as an anode and a titanium plate as a cathode, place them in the colloidal solution prepared above, apply a voltage of 2-30V, and deposit for 60-600s; S6: The deposited coating is treated under high-temperature inert gas protection at a temperature of 950°C-1250°C and a heat preservation time of 60min-180min.
3. The method for preparing the conductive corrosion-resistant coating of titanium bipolar plate according to claim 2, characterized in that: Prior to S1, this also included: S0: Titanium plate pretreatment First, the titanium plate is ground and polished, and then the titanium plate is ultrasonically cleaned; Then, the titanium plate is etched with a mixture of hydrofluoric acid and nitric acid for 20 to 60 seconds, and then ultrasonically cleaned with deionized water to obtain a pretreated titanium plate.
4. The method for preparing the conductive corrosion-resistant coating of titanium bipolar plate according to claim 2, characterized in that: After S5, it also includes: S51: After the electrophoretic deposition process is completed, the sample is placed in a vacuum drying oven at 60° C. for vacuum drying for 12 h, and then vacuum dried at 100° C. for 1 h.
5. The method for preparing the conductive corrosion-resistant coating of titanium bipolar plate according to claim 2, characterized in that: The S6 specifically includes: The dried sample is placed in an alumina crucible, put into a tubular furnace, and heated to 950-1250°C at a heating rate of 5°C / min under the protection of high-purity argon for heat treatment, and kept at this temperature for 60-180 minutes. After cooling in the furnace, a conductive and corrosion-resistant composite coating is obtained.
6. The method for preparing the conductive corrosion-resistant coating of titanium bipolar plate according to claim 2, characterized in that: In S1, the provided In2O3 and SnO2 mixed powder, wherein the molar amount of Sn element in the mixed powder accounts for 0-100% of the total molar amount of In and Sn.
7. The method for preparing the conductive corrosion-resistant coating of titanium bipolar plate according to claim 2, characterized in that: The material of the titanium plate is a titanium plate with a Ti content greater than 80wt.%.
8. The method for preparing the conductive corrosion-resistant coating of titanium bipolar plate according to claim 2, characterized in that: The colloidal solution in step S2 is a 12 g / L colloidal solution prepared with anhydrous ethanol as solvent, which contains 1.56 g of mixed powder of In2O3 and SnO2 and 130 ml of anhydrous ethanol, and the molar amount of Sn element in the mixed powder accounts for 4.6% of the total molar amount of In and Sn.
9. The conductive and corrosion-resistant coating for titanium bipolar plates according to claim 1, characterized in that: The electrochemical parameters of the coating are: At 70℃, 0.5mM H2SO4+5ppm F - The corrosion potential E of the coating compared to the silver-silver chloride electrode in the electrolytic cell anode working solution environment corr is -95.9mV, the corrosion current density I corr 0.258μA / cm 2 , the interface contact resistance ICR is 15.94mΩ·cm 2 .
10. An anode titanium plate for a proton exchange membrane electrolyzer, characterized in that: The invention comprises a titanium base layer, and the coating as claimed in claim 1 covering the titanium base layer.